Epidemiological patterns and clinical presentations of ectopic pregnancy in a tertiary hospital: a prospective observational study - Shahrin, Sadia; Mahfuza, Gazi; Begum, Manira; Akter, Roksana; Biswas, Joyti R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Ectopic pregnancy is a potentially life-threatening condition where a fertilized egg implants outside the uterus, most commonly in the fallopian tubes. It poses significant risks to the health and well-being of women of reproductive age. This study aims to explore the epidemiological patterns, clinical presentations, and risk factors associated with ectopic pregnancy in a tertiary hospital setting. Methods: This prospective observational study was conducted at the Department of Obstetrics and Gynaecology, Rajshahi Medical College Hospital, Rajshahi, from January 2014 to June 2014. A total of 45 patients were selected as study subjects by purposive sampling technique. Statistical analysis was carried out by using the statistical package for social sciences (SPSS) version 16.0 for Windows. Results: The study found that most ectopic pregnancy patients were aged 21-25 years, with 93.3% having ruptured ectopic pregnancies. A majority (60.0%) had 6-8 weeks of amenorrhea, and 46.7% had one prior pregnancy. Common symptoms included abdominal pain, amenorrhea, shock, and per vaginal bleeding, with abdominal pain present in all cases. Acute presentations, such as massive hemorrhage and cardiovascular collapse, were seen in 57.78%, while 35.56% had acute-on-chronic symptoms. Clinical signs often included abdominal tenderness, distention, and a positive cervical excitation test. Conclusions: The study highlights the significant burden of ectopic pregnancy among women of reproductive age, particularly those between 21 and 30 years. The majority of cases were ruptured (93.3%), often presenting as acute emergencies with massive intraperitoneal hemorrhage and cardiovascular collapse. Abdominal pain was a universal symptom, while vaginal bleeding was present in most ruptured cases. Clinical findings commonly included abdominal tenderness, cervical excitation, and abdominal distension.